Benefits and Risks of Rapid Initiation of Antiretroviral Therapy: A Systematic Review and Meta-Analysis - Bai, Ruojing; Du, Juan; Lv, Shiyun; Hua, Wei; Dai, Lili; Wu, Hao (Frontiers in Pharmacology, 2022)
Objectives: To compare the benefits and risks between Rapid ART and standard/delayed treatment for HIV. Methods: Databases of PubMed, Cochrane Library, Embase and Web of science were searched from the inception to October 28, 2021. Two investigators independently screened studies related to Rapid ART, extracted data, and evaluated the literature quality. The risk of bias was assessed by Cochrane Collaboration Risk of Bias Tool and the statistical software Stata15.0 was used for meta-analysis. Results: Ten eligible studies were included in this meta-analysis, the results showed Rapid ART was superior to standard/delayed treatment in continuing care for at least 8 months [RR=1.13, 95%CI: 1.03~1.25, Z=2.44, P=0.015], and severe bacterial infection [RR=0.42, 95%CI: 0.25～0.70, Z=3.33, P=0.001]. There was no statistically significant difference in viral load < 100 copies/mL at 12 months after treatment [RR=1.05, 95%CI: 0.80~1.39, Z=0.35, P=0.726], mortality [RR=0.77, 95%CI: 0.47~1.24, Z=1.09, P=0.277], or the incidence of adverse events [RR=0.52, 95%CI: 0.16~1.76, Z=1.05, P=0.294] compared with standard/delayed treatment. Conclusions: Rapid ART can reduce the risk of tuberculosis and severe bacterial infections in HIV patients compared to standard/delayed treatment. Our findings provide Rapid ART is suggested to be used when medical conditions and the patient's physical conditions permit.